Clinical Indicators of Surgical Outcomes After Laminoplasty for Patients With Cervical Ossification of the Posterior Longitudinal Ligament: A Prospective Multicenter Study. Issue 15 (1st August 2022) - Nagoshi, Narihito; Yoshii, Toshitaka; Egawa, Satoru; Sakai, Kenichiro; Kusano, Kazuo; Tsutsui, Shunji; Hirai, Takashi; Matsukura, Yu; Wada, Kanichiro; Katsumi, Keiichi; Koda, Masao; Kimura, Atsushi; et al.
Abstract : Study Design: A prospective multicenter study. Objective: This study aims to evaluate patient-reported outcomes using the Japanese Orthopedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ) and clarify clinical factors that affect the therapeutic effects for patients with cervical ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: Although previous studies identified factors that affected the surgical outcomes, their assessment was mainly based on the Japanese Orthopedic Association score, which only includes neurological function. Investigating this pathology through multiple functions and quality of life (QOL) is pivotal to understanding the comprehensive clinical pictures of the cervical OPLL and its therapeutic outcomes. Materials and Methods: This study was performed by the Japanese Multicenter Research Organization for Ossification of the Spinal Ligament. A total of 478 patients with myelopathy caused by cervical OPLL from 28 institutions were prospectively registered from 2014 to 2017 and followed up for 2 years. Of the patients, 168 received laminoplasties and fully completed questionnaires. Demographic information, imaging findings, and clinical outcomes were collected. Patients were grouped according to effective or ineffective surgical outcomes as defined by the JOACMEQ using logistic regression analyses. Results: Laminoplasty resulted in functional improvement in the cervical spine and upper extremity around 40% of the patients, while QOL showed only 21.4% ( P <0.01). Multivariable analyses revealed that younger age and a postoperative decrease in arm or hand pain were correlated with significantly improved function of the upper extremities. A reduction in lower limb pain favorably affected the postoperative lower extremity function. A postoperative reduction in upper extremity pain enhanced the QOL recovery. Conclusions: Surgeons should recognize the diversity of surgical outcomes after laminoplasty and understand the necessity of pain management even after the surgery to enhance bodily functions and QOL in patients with cervical OPLL.